How to plan development of municipalities and barangays - Calling, Gemiliano C. (Manila Rex Book Store, 1991)
This contains the elements, processes, and linkage necessary for local development and planning of city, municipal and barangay executives and officials. It can also be used by sectoral groups, non-government organizations, and individuals. It deals with all aspects of socio-economic and physical development planning, programming and budgeting. It is arranged chronologically as follows: (1.) rationale of development planning, (2.) preparation of socio- economic development plan, (3.) formulation of investment programs and budgets, (4.) planning barangay development, (5.) planning physical development, (6.) implementation of local government plan, and (7.) realization of barangay development. Text is supplemented by tables and figures. A subject index is provided.
Keywords: Regional planning -- Philippines; Local government -- Philippines; Planning -- Philippines